2011
DOI: 10.1080/00219266.2011.537842
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in a test tube: rise of the Wrinkly Spreaders

Abstract: Understanding evolutionary mechanisms is fundamental to a balanced biological education, yet practical demonstrations are rarely considered. In this paper we describe a bacterial liquid microcosm which can be used to demonstrate aspects of evolution, namely adaptive radiation, niche colonisation and competitive fitness. In microcosms inoculated with Pseudomonas fluorescens SBW25, evolved mutants such as the Wrinkly Spreader (WS) rapidly arise to form biofilms covering the air-liquid (A-L) interface. WS are rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 4 publications
1
32
0
Order By: Relevance
“…Most labs exploring macroevolutionary change have relied on comparisons with living lineages, fossils, or computer simulations (Dubowsky and Hartman 1986;Rodrígues et al Rodríguez et al 2006;Soderberg and Price 2003). While these are valuable teaching materials, inquiry based exercises that utilize living organisms can be more transparent, and offer a direct connection to the ecological theater in which evolutionary processes play out (Delpech 2009;Green et al 2011;Olson and Loucks-Horsley 2000;Plunkett and Yampolsky 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Most labs exploring macroevolutionary change have relied on comparisons with living lineages, fossils, or computer simulations (Dubowsky and Hartman 1986;Rodrígues et al Rodríguez et al 2006;Soderberg and Price 2003). While these are valuable teaching materials, inquiry based exercises that utilize living organisms can be more transparent, and offer a direct connection to the ecological theater in which evolutionary processes play out (Delpech 2009;Green et al 2011;Olson and Loucks-Horsley 2000;Plunkett and Yampolsky 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This work, described in the following section, ultimately showed that the evolutionary innovation was the use of cellulose to produce a physically robust and resilient biofilm which allowed the colonisation of the A-L interface. Competitive fitness experiments have demonstrated that the WS has a significant fitness advantage over non-biofilm-forming strains in static microcosms [5,11,49]. Simplistically, WS cells were able to intercept O2 diffusing across the A-L interface from the atmosphere before non-biofilm-forming competitors could do so lower down the liquid column, and as a result, WS populations could grow more rapidly than non-WS populations [53].…”
Section: Experimental Evolution and The Wrinkly Spreadermentioning
confidence: 99%
“…Simplistically, WS cells were able to intercept O2 diffusing across the A-L interface from the atmosphere before non-biofilm-forming competitors could do so lower down the liquid column, and as a result, WS populations could grow more rapidly than non-WS populations [53]. In contrast however, the WS do not enjoy a fitness advantage in shaken microcosms where the O2 concentrations are uniform or on agar plates where the WS phenotype is unstable [5,[48][49].…”
Section: Experimental Evolution and The Wrinkly Spreadermentioning
confidence: 99%
See 1 more Smart Citation
“…Colonisation of the A-L interface by the Wrinkly Spreader allows better access to O 2 diffusing into the liquid column from the air above, providing a competitive fitness ( W ) advantage over the ancestral wild-type P. fluorescens SBW25 and other non-biofilm-forming mutants whose growth is O 2 -limited deeper into the microcosm [9, 11, 14, 21]. This advantage may reflect a significant change of physiology, as biofilm-isolated cells growing in the high-O 2 zone can be differentiated from those recovered immediately below the biofilm by Raman spectral profiling [22] ( P. fluorescens SBW25 can form a different type of biofilm when induced with Fe 3+ which also provides a fitness advantage [23]).…”
Section: Introductionmentioning
confidence: 99%